Dyes in post-byzantine and Ottoman textiles: A comparative HPLC study - (:unkn) unknown (University of AEGEAN, 2015)
The goal of the study is to compare the dyes used in ecclesiastical post-Byzantine (sixteenth to early twentieth century) textiles of Mount Athos, Greece, with the corresponding organic colourants used in Ottoman (sixteenth to eighteenth century) textiles which are preserved in the Topkapi Palace Museum, Turkey. During the historical period of interest, Mount Athos which has been the spiritual centre of Byzantine culture for centuries, was within the borders of the Ottoman Empire (period of Ottoman rule). Samples extracted from forty-six and fifty post-Byzantine and Ottoman textiles, respectively, were analysed using high performance liquid chromatography with diode array detection (HPLC–DAD). The analysis of a silk velvet (Topkapi Palace Museum) is presented in detail and serves as an example to describe the methodology that was applied throughout the investigation. More similarities than differences are observed in the results reported for the two textile collections of different cultural identity. The following materials were found in both post-Byzantine and Ottoman textiles: cochineal, madder, lac, young fustic, weld, dyer’s broom, buckthorn berries, indigo/woad and tannins. On the other hand, soluble redwood, old fustic and logwood were found only in post-Byzantine textiles while dyer’s chamomile and Rumex species were detected only in few Ottoman objects. © 2015 MAA Open Access. Printed in Greece. All rights reserved.
Keywords: Byzantine; Dye; HPLC; Ottoman; Textile